Experimental research on sealing performance of liquid film seal with herringbone-grooved composite textures. (February 2023) - Fuyu, Liu; Yongfan, Li; Bo, Yu; Muming, Hao; Xinhui, Sun; Zhentao, Li; Lushuai, Xu
Abstract: Based on the mechanical seal experiments, sealing performances of the mechanical face seals with the herringbone-grooves (HG) only and with composite textures of herringbone grooves and circular dimple textures (HGC) were investigated respectively. The reserve suction effect of HG observed in the experiments provided the evidence for the main inducing mechanism of zero leakage in liquid film sealing. The cavitation region of HGC decreases with the rotating speed, and the HG has the reserve effect. The HGC has lower friction torque and larger film thickness compared to HG, indicating better friction performance. Because of the circular dimples, the temperature difference in sealing rings is reduced and the corresponding thermal performance of the mechanical seal has been improved. Highlights: Compositing circular dimple textures in herringbone-grooved seals reduce the friction torque and improve the lubrication. Composite circular dimple textures could inhibit cavitation development with increasing rotational speed. Cavitation suction effect could achieve the zero-leakage of liquid film seal. Temperature differences of stator reduced by compositing circular dimples.